PENGEMBANGAN MEDIA CLASSROOM MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Otorifa Halawa; Bezisokhi Laoli; Arianto Lahagu; Wahyutra Adilman Telaumbanua (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
The lack of student participation in each lesson is caused by the learning model that is still conventional. The purpose of this study is to improve student learning outcomes through the development of classroom media using the problem-based learning model. The research method used is the research and development method. Based on the results of the study, it is known that the PBL-based Google Classroom media is considered very feasible. This indicates that the media created has met the requirements for ease of use, instructional design, and content quality. The results of the media usage test indicate that student learning outcomes have improved. This is evidenced by comparing the results of the pre-test and post-test of students, which increased significantly after using the PBL-based Google Classroom media. Students also showed improvements in critical thinking capacity, teamwork, and active participation in the learning process, as well as being more motivated to learn, and more active in completing problem-based tasks.